How the political participation of refugees is shaped on the local level: Self-organisation and political opportunities in Cologne - Milan Jacobi (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Six years have passed since the so-called 'long summer of migration' of 2015, and the numbers of newly arriving asylum-seekers in Germany have flattened. However, as one of the main receiving countries of refugees, other challenges are coming into focus. Besides labour market participation and cultural participation, political participation is crucial to social life. But how to enable the political participation of refugees in host countries remains a challenge. This study examines how refugees without the condition of citizenship, who, thus, lack formal, electoral means of participation, can engage in political activities. To this end, it first uses a qualitative approach to examine how various self-organisations in the city of Cologne, Germany, use their resources to bring their interests into the political decision-making process. Second, it examines the political opportunity structures that exist at the local level to enable refugee self-organisations (RSOs) to engage in political activities. For this purpose, interviews were conducted with representatives of the organisations as well as the municipality and other civil society actors in Cologne. The results show that RSOs can be important partners for municipal decision-makers when it comes to refugee-specific issues. However, the results also suggest that opportunity structures are unevenly distributed among organisations and affect the organisations' resource endowments, thus limiting access.
Keywords: 330; Flüchtlinge; Politische Partizipation; Politische Entscheidung; Selbstorganisation; Gemeinde; Köln; Deutschland